Analisis Perawatan pada Pipa Superheater di Unit Boiler 1 menggunakan Metode Risk Based Inspection - Ozkar F. Homzah; Ella Sundari; Vera Octavia (Universitas Sriwijaya, 2023)
The failure of the superheat pipe is one of the important problems that often occur in steam power plants, this is caused by thinning on the surface due to abrasion by silica sand contained in the combustion gas flow continuously during operation. Based on the failures that occurred in the boiler pipes in the 3x10 MW TE unit, this is very risky and has a major effect on electricity production. In addition, this also causes considerable financial problems due to downtime. In this study, we used the risk-based inspection method to provide an overview of the inspection schedule plan. As a result, based on the API 581 standard, the probability of failure is category 5 and the financial risk is level C. Therefore, the risk level of the superheat is medium-high. Conditionally, we expect the power plant to run the inspection schedule 27 days after the failure report based on the thickness measurement.